The winds of low-mass stars and solar-wind evolution - Ó FIONNAGÁIN, DÚALTA AODH (Trinity College Dublin. School of Physics. Discipline of Physics, 2020)
Stellar winds affect the evolution of stars (as well as impacting the planets orbiting these stars) through the removal of angular momentum and mass over time. This process changes the rotation rate of the host star, which in turn affects the stellar wind. The Sun is the only star for which there are in situ wind measurements, and those present day values do not reflect the past and future states of the solar wind. Throughout this thesis, I research the evolution of the solar wind using numerical simulations (in 1D, 3D, HD, and MHD) of the winds of similar low-mass stars. I focus on examining the evolution of these winds and the effects these winds can have on the exoplanets that are embedded within them. The temporal trends of solar-mass stars along the main sequence is quantified in terms of mass-loss rate and angular momentum-loss rate, with both quantities decreasing as the star ages. This is important as it provides information on the evolutionary stage of the star and the age-rotation relationship. From the simulations in this thesis, I was able to examine the environments of orbiting exoplanets, by studying the effects the local wind conditions would cause on the orbiting planet. These quantities can have significant impacts on the evolution of the planet and in particular the planetary atmosphere. I examine the wind of lambda Andromedae, a solar-mass star which has evolved off the main sequence to become a sub-giant star. This is the first 3D MHD study into an evolved solar-mass stellar wind, and I do so using both polytropic and Alfvén wave-driven winds. I show that a thermal, thermally-driven wind driven from a hot corona best replicates the radio observations of this star. As stellar winds permeate the entire region from the star to the interstellar medium, orbiting planets experience the direct impact of evolving stellar winds. This causes the planets' magnetospheres and atmospheres to change over long timescales, leading to significant effects on our understanding of planetary evolution and their atmospheres. The presence, removal, or lack of an atmosphere will drastically change the surface conditions on a planet. My research provides the astronomy community with wind conditions to estimate the effects of stellar winds on any planets orbiting these low-mass stars, as well as the evolution of conditions around the Earth and Mars. I show that in the past the magnetosphere of the Earth would have been much smaller than the present day size. For more extreme exoplanetary systems, close-in exoplanets can directly interact with their host stars through magnetic processes in their winds or magnetospheres. Although not a new concept, the study of star-planet interactions is evolving due to advances in instrumentation leading to exciting new discoveries and supporting evidence for this phenomenon. I simulate the wind of 55 Cancri, which possesses a system of 5 exoplanets, and show that magnetic star-planet interactions are not only possible, but probable in the case of the closest planet, 55 Cancri e. I quantify the phenomenon using the wind conditions between the planet and star and show any emission is likely to be quite transient and difficult to observe with complex temporal signatures, but possible given long observational monitoring or serendipitous observations. Stellar winds emit radiation in the form of thermal bremsstrahlung in the radio regime as expected from an ionised plasma. This emission could be an indicator for important wind quantities such as mass-loss rate and density. Unfortunately, to date, no low-mass stellar winds have been detected in the radio regime due to their tenuous nature, however non-detections and upper limits still provide meaningful constraints on the same wind parameters. However, disentangling this emission from other radio sources in the stellar system can be difficult. To aid in the detection of radio emission from low-mass stellar winds I analytically and numerically calculate the thermal radio flux densities expected from the stellar winds I simulated, at frequencies where they are expected to possess the strongest flux density. Currently, only upper-limits exist for the observations of these stellar winds. I predict the flux density expected from a number of solar-mass stars, showing that within the next generation of radio telescopes, the additional sensitivity should allow the community to detect some of these winds directly. These studies are also relevant when searching for any other radio emissions from star-planet systems, as it is important to quantify emission from the stellar wind so it can be properly accounted for. The novel research carried out in this thesis has explored the long-term evolution of the solar wind using numerical simulations, and analysed the significant changes experienced by the host star and orbiting planets. The various results presented here have succeeded in quantifying this relationship between wind evolution, the host star, and orbiting planets. Future research into the winds of low-mass stars spans a wide-range of possible avenues including star-planet interactions, wind radiation, temporal events (CMEs, flares), and planetary atmospheric and magnetospheric evolutionary trends.
APPROVED